Welfare or Workfare?: The Principle of Activation in the Finnish Post-War Disability Policy, Early 1940s to late 1980s. (7th September 2015) - Leppälä, Heli
Abstract: This article analyzes the post–Second World War Finnish discussion on disability pension and vocational rehabilitation policies. It argues that the principle of activation, which has been linked to the recent neoliberal workfare turn in social policy, has in fact remained as one of the guiding principles of disability policy during the entire post-war period. During the 1940s, the Finnish disability policy was established on the principles of compensation and activation, as the disability pension scheme was limited to those who had participated in working life and vocational rehabilitation to those who were evaluated to have the potential to do so in the future. At the turn of the 1960s, the compensation principle was overtaken by the principle of need as the newly adopted goal of constructing the Finnish welfare state materialized in the demands for a universal pension policy and extending vocational rehabilitation to those who had previously been labeled as unprofitable targets. However, the traditional disability policies began to receive criticism during the 1980s as the conception of disability changed from being viewed as an individual defect raising a need for segregated services and environments to a minority status entitling a person to supportive measures enabling him or her to participate in the normal society. This also problematized the traditional divide between the need-based and work-based systems of distribution by raising the question on disability pensioners' entitlement to participate in the labor market.